Bifunctional antibiotic hybrids: A review of clinical candidates - Koh, Augustine Jing Jie; Thombare, Varsha; Hussein, Maytham; Rao, Gauri G.; Li, Jian; Velkov, Tony (Frontiers in Pharmacology, 2023)
Antibiotic resistance is a top threat to human health and a priority across the globe. This problematic issue is accompanied by the decline of new antibiotics in the pipeline over the past 30 years. In this context, an urgent need to develop new strategies to combat antimicrobial resistance is in great demand. Lately, among the possible approaches used to deal with antimicrobial resistance is the covalent ligation of two antibiotic pharmacophores that target the bacterial cells through a dissimilar mode of action into a single hybrid molecule, namely hybrid antibiotics. This strategy exhibits several advantages, including better antibacterial activity, overcoming the existing resistance towards individual antibiotics, and may ultimately delay the onset of bacterial resistance. This review sheds light on the latest development of the antibiotic hybrids pipeline, their potential mechanisms of action, and challenges in their use.